2014
DOI: 10.1177/1076029614551823
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel Plus Aspirin Prevents Early Neurologic Deterioration and Improves 6-Month Outcome in Patients With Acute Large Artery Atherosclerosis Stroke

Abstract: Clopidogrel plus aspirin is superior to aspirin alone for reducing END and RIS within 30 days and improves outcomes in certain subgroups at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 45 publications
2
39
0
Order By: Relevance
“…We fully agree with the authors who customized antiplatelet therapy based on platelet function assays and their results that showed lower rates of recurrent events after platelet reactivity-guided modification of therapy [22,23]. In addition, there have been reports about dual antiplatelet therapy (ASA plus clopidogrel) that could be effective and beneficial for the large artery atherosclerosis etiologic subtype of stroke [24,25] and that dual antiplatelet therapy is associated with a lower risk of HTPR [7]. Considering the results obtained in our study, this provides further support for updating the stroke guidelines and recommendations.…”
Section: Discussionsupporting
confidence: 76%
“…We fully agree with the authors who customized antiplatelet therapy based on platelet function assays and their results that showed lower rates of recurrent events after platelet reactivity-guided modification of therapy [22,23]. In addition, there have been reports about dual antiplatelet therapy (ASA plus clopidogrel) that could be effective and beneficial for the large artery atherosclerosis etiologic subtype of stroke [24,25] and that dual antiplatelet therapy is associated with a lower risk of HTPR [7]. Considering the results obtained in our study, this provides further support for updating the stroke guidelines and recommendations.…”
Section: Discussionsupporting
confidence: 76%
“…In particular, dual antiplatelet therapy (aspirin and clopidogrel) with high-intensity statin was prescribed in those patients for several months according to a guideline from the American Heart Association and American Stroke Association [ 23 ]. This practice is further supported by the results of a recent study showing that a short course (a month) of dual antiplatelet therapy reduced END and stroke recurrence in patients with acute LAA stroke [ 24 ]. Noticeably, the effect of dual antiplatelet therapy was higher in patients with posterior circulation stroke and basilar stenosis in that study.…”
Section: Discussionmentioning
confidence: 72%
“…Our previous studies and some other studies have shown that platelet activation plays a key role in the pathogenesis of IS and RIS [Marquardt et al . 2002; Wang et al . 2015; Yi et al .…”
Section: Discussionmentioning
confidence: 99%